2014
DOI: 10.3109/09687637.2014.899987
|View full text |Cite
|
Sign up to set email alerts
|

Service user, family and friends’ views on the meaning of a ‘good outcome’ of treatment for an addiction problem

Abstract: in fo rm a h e a lth c a re S ervice user, fa m ily and frie n d s ' view s on th e m ean in g o f a 'good o u tc o m e ' o f tre a tm e n t fo r an a d d ic tio n p ro b le m Aims: The aim of this study was to investigate the views of service users (SUs), family and friends on what constitutes a good outcome for the treatment of substance misuse problems.Methods: Six focus groups were arranged to explore and identify important elements of good outcome. Transcripts of the focus groups were analysed using thema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Failure to involve patients in the process of outcome measurement raises the possibility that measurement overlooks aspects of relevance for patients and over-optimistic reporting of outcomes (Thurgood et al, 2014). Increasingly, studies are seeking the views of patients about outcome measurement criteria (e.g., Ruefli and Rogers, 2004;Neale et al, 2016;see Table 1).…”
Section: Does Outcome Measurement Reflect the Concerns Of Patients?mentioning
confidence: 99%
“…Failure to involve patients in the process of outcome measurement raises the possibility that measurement overlooks aspects of relevance for patients and over-optimistic reporting of outcomes (Thurgood et al, 2014). Increasingly, studies are seeking the views of patients about outcome measurement criteria (e.g., Ruefli and Rogers, 2004;Neale et al, 2016;see Table 1).…”
Section: Does Outcome Measurement Reflect the Concerns Of Patients?mentioning
confidence: 99%
“…This perspective would also need to consider individual variation in participant's identification and prioritization of goals [64]. Some empirical research has been underway to develop [65,66] or inform the development of patient-reported outcome measures in substance use treatment [67][68][69][70]. However, ongoing research is needed to determine how such tools reflect individually based goals and outcomes in MAT with oral and injectable opioids.…”
Section: Discussionmentioning
confidence: 99%
“…These instruments are mostly based on criteria selected by experts, which do not always coincide with what patients deem important (Pulford et al 2009;Thurgood et al 2014). A recent study has attempted to overcome this limitation by including patients in the development of a standardised outcome measure, involving them in topic selection .…”
Section: Outcome Assessment In Substance Use Treatmentmentioning
confidence: 99%